Effects of corn distiller grains or corn gluten feed as a replacement for soybean meal in Boer goats - Grider, Kristin E.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
There is little published information on corn co-product effects when incorporated into goat diets. This study hoped to gain knowledge on what would be most effective and economically efficient diet to enhance goat growth performance. The objective of this experiment was to compare the growth performance and cost efficiency of corn gluten feed (CGF) or corn dried distiller grains (DDGS) as a substitute for soybean meal in Boer type goats. Seventy-five Boer-type goats with an average weight of 26.9±0.2 kg and age of 70 days were randomly assigned to one of the five treatments for 35 d. Pen was the experimental unit, with 3 goats/pen and 5 pens/treatment. Five treatments varied in protein sources, but were isonitrogenous and isocaloric, including 1) 100% DDGS/0% CGF (control), 2) 66% DDGS/33%CGF, 3) 66% DDGS/33% CGF, 4) 33% DDGS/66% CGF, and 5) 0% DDGS/100% CGF. Measured criteria were calculated weekly, including BW, ADG, ADFI, G:F, feed cost/kg of gain, and feed cost/kg of goat. GLIMMIX procedure was used to analyze data (SAS Inst., Cary, NC). There were no detected differences in final BW, ADG, ADFI, F:G, or cost/kg of gain by the experimental treatments (P > 0.05). However, the corn DDGS and CGF diets had a lower feed cost/goat (P = 0.0008) than the soybean meal. Overall, this experiment supports corn co-products, corn DDGS and CGF, being economically efficient enough to replace soybean meal in goat diets focusing on growth.
Keywords: Spring 2019